Managing the waste rock storage design — can we build a waste rock dump that works? - Barritt, R; Scott, P; Taylor, I (Mine Closure 2016: Proceedings of the 11th International Conference on Mine Closure, 2016)
For a waste rock dump to be managed both during operations and at closure, a thorough understanding of the composition of the waste is an important requirement. A comprehensive block model should be prepared, with an appropriate materials management and placement plan developed in conjunction with the mining schedule. However, a waste rock dump’s success is hinged on such compositional elements being regularly updated through ongoing materials characterisation over the life-of-mine. Failure to undertake this may potentially result in inappropriate material placement and classification for environmental purposes, and unnecessary costs to the mine and surrounding environment. A revised cover system and landform design was undertaken for a base metal mine in northern Australia following reclassification of its waste. The original permitted landform design comprised an extensive protective cover system of non-acid forming waste rock (88% of overall waste), encapsulating the small potentially acid forming waste volume (12% of overall waste). Additional geochemical studies indicated that these ratios were incorrect and as such, the total volume of clean non-acid forming waste available for the facility was further decreased to a fraction of the initial value. A cover system incorporating both the barrier and moisture ‘store-and-release’ concepts was proposed to limit net percolation into the reactive potentially acid forming waste. In addition, a landform design and extensive surface water management plan was prepared to manage both the high intensity wet season rainfall received at site and the naturally erosive materials available for landform construction. This paper presents the issues encountered during the design stage, which included: a tropical climate; geochemically reactive waste materials; and a surface water management system design, which was to be maintenance free and similar to natural systems in the long term.
Keywords: mine closure